Examining Digital Entrepreneurship: The Goal of Optimization of Transformation Path Normal Education in China - Zhao, Yang (Frontiers in Psychology, 2021)
The education system in China needs optimization with the erupted pandemic for effective outcomes. The path for the normal education is upgrading itself with online learning, hence offering a challenge for entrepreneurship. The education sector needs to tackle these offered challenges in a better way that optimizes and exploits the situations. Not only that, the way teachers and students communicate and utilize their learning into materializing new ideas is very important for keeping the pace. Therefore, this study investigates the role of mentorship in digital entrepreneurship. The population for the study was the teachers of normal education in China. The sampling design used was convenient random sampling and data was collected with a self-administered questionnaire on five point Likert scale. This study has used Smart PLS 3.3.3 for the data analysis through structural equation modeling. In first stage, the measurement model was analysed for the instrument and in second stage the hypotheses were checked using the data collected. The findings of the study show that mentorship is playing a very important role in knowledge sharing and innovation, that further leads to digital entrepreneurship. The study will opens new path in the education filed to in corporate the knowledge hidings and transformational entrepreneurship.